A preliminary screening of single nucleotide polymorphism (SNP) of A1 and A2 beta-casein alleles in dairy cattle - Nadiatur Akmar Zulkifli,; Nurhafizatul Ain Baharim,; Sharifah Salmah Syed Hussain, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Milk containing A1 variants in the beta-casein gene is considered to be a risk factor for coronary heart disease (CHD), type I diabetes (DM-I), autism, and schizophrenia due to the release of beta-casomorphin 7 (BCM-7). The objectives of this study were to screen for polymorphism of beta-casein in dairy cattle and to examine the allelic and genotypic frequencies of A1 and A2 variants. A total of 290 cattle blood samples were collected from two states and the samples were extracted. This was followed by PCR amplification for exon 7 of the beta-casein gene (CSN2). The PCR products were then subjected to DNA sequencing. The sequencing results were aligned and the variants were screened. In Pahang, 125 samples are of the A2A2 genotype, followed by A1A2 (n=97) and A1A1 (n=28). While in Melaka, the highest genotype was A2A2 (n=20) as compared to A1A2 (n=18) and A1A1 (n=2). Meanwhile, the frequency of the A2 allele was higher than A1 in both states. The high genotypic frequencies of A2A2 in these cattle populations could be influenced by the cattle breed as well as the rate of crossbreeding on the farm. Thus, screening of dairy cattle for A1 and A2 beta-casein could be used in selecting the preferred animals for breeding.